EPISTEMOLOGY OF TAFSIR PESANTREN: Portrait of Qur’anic Interpretation Studies by KH. Muhammad Shalahuddin - Syaiful Bahri; Luthfi Raziq; Fadhilah Khunaini (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract Pesantren does not only teach the Qur’an but also tafsir with the finished classical books of tafsir, like Tafsîr Jalalayn, Ibnu Katsîr, and others. On the contrary, study of tafsîr in PP. Annuqayah of Lubangsa area is not focused on of those books only, it is personally delivered by KH. Muhammad Shalahuddin leaving the finished classical book of tafsir. This article would like to expres how the methodology of KH.Muhammad Shalahuddin Qur’anic interpretations is? And how the contextualization of KH. Muhammad Shalahuddin Qur’anic interpretations is? The theories which are used to frame those questions are the methodology of Islah Gusmian and contextual approach of Abdullah Saeed. This is compiled by using qualitative-descriptive method, by field research approximation. It shows: First, the methodology of KH Muhammad Shalahuddin Qur’anic interpretations is using is serial presentation based on serial of chapters in standard model of mushaf with detail presentation form. It is using reporting literary style. It is included in non-scientific writing form. It comes from non-academic spaces, but it uses thought interpretation method with semiotic analysis and contextual approach which full of social nuance; Second, the contextualization of KH Muhammad Shalahuddin Qur’anic interpretations appears in the Qur’an chapter al-Baqarah 30-35 which is included into instructional values among the five hierarchy values. By completing four stages which are formulated by Abdullah Saeed, KH. Muhammad Shalahuddin contextualizes the comprehension to the verses with various social contemporary common accidents around the boarding school. He directs the social wisdom from the verses for any problems today. Keywords: Methodology, Contextualization, KH. Muhammad Shalahuddin